2012
DOI: 10.21236/ada579696
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Low-Velocity Impact and Quasi-Static Indentation

Abstract: Approved for public release; distribution is unlimited.ii REPORT DOCUMENTATION PAGE Form Approved OMB No. 0704-0188Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection information. Send comments regarding this burden estimate or any other aspect of this collection of information, including sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Many researchers have investigated low-velocity impact and equivalent quasi-static indentation loading [9][10][11]. By contrast, systematic studies of damage tolerance in CAI tests are far fewer in number.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have investigated low-velocity impact and equivalent quasi-static indentation loading [9][10][11]. By contrast, systematic studies of damage tolerance in CAI tests are far fewer in number.…”
Section: Introductionmentioning
confidence: 99%
“…Nettles and Douglas [11] and Lee and Zahuta [13] also state that these two tests induce similar failure mechanism, with very similar damages and force × displacement curves, for carbon/epoxy composites. On the contrary, Lawrence et al [14] and Spronk et al [15] reported different damages and curves from QSI and drop-weight tests for glass-S2/epoxy, carbon/epoxy and glass/polyamide composites.…”
Section: Resultsmentioning
confidence: 96%
“…Since there are many different production parameters in impact tests, tests were performed according to ASTM D7136 standard at a constant energy of 50 joules. 56 Production parameters were compared by considering the force deformation curves as test results. The specimen dimensions are 100 mm × 100 mm square.…”
Section: Impact Test Resultsmentioning
confidence: 99%